Parietal peritoneal closure versus non-closure at caesarean section: which technique is feasible to perform? - ÖZCAN, PINAR; Altinbas, Sadiman Kiykac; Cenksoy, PINAR; Tapisiz, Omer Lutfi; Beydilli, Gulay; Yirci, Bulent; Ercan, Onder; Dede, Suat; Kandemir, Omer (My University, 2013)
Objective: To evaluate short-term effects of closure versus non-closure of the parietal peritoneum at caesarean section.